Korelasi Kemiskinan dan Persepsi Kualitas terhadap Probabilitas Menyuap dalam Pelayanan Publik : Studi Kasus Indonesia - Naibaho, Maria Patricya; Gultom, Yohanna (Jurnal Kebijakan Ekonomi, 2020)
The study attempts to find out to what extent "grease the wheels" hypothesis can explain the bribery phenomena in Indonesia that has been done by the poor to access public services like public administration, police, health, and education. The study used cross-section data from a national survey of the Public Perception of the Corruption Trend 2018 conducted by Lembaga Survey Indonesia (LSI). The survey’s respondents are 3,670 households spread in 34 provinces in Indonesia. The study shows that the grease the wheels hypothesis is found only in health sector, confirming that the characteristics of the public services determine the likelihood of the poor to bribe when the quality of the public service is poor. The result of logit regression shows that the odds ratio of the poor people that have a bad perception on the quality of public service to bribe increases by a factor of 7,61 compared to the poor people that have good perception on the quality of public service. This shows that the characteristics of public services, such as the level of rivalry, cost of alternative services, and the risk to be excluded from the public service are the determinants of bribery in public services.